REKONSTRUKSI MANAJEMEN MUTU PESANTREN MELALUI PENDEKATAN TOTAL QUALITY MANAGEMENT (TQM) - Bukhori, Ahmad (Jurnal Studi Pesantren, 2024)
Pesantren as a traditional educational institution plays an important role in shaping the character and personality of the younger generation. However, in order to remain relevant and high-quality in facing the challenges of the modern era, pesantren need to update and improve their quality management systems. This article proposes a Total Quality Management (TQM) approach as a framework for reconstructing the quality management of pesantren. Through this approach, pesantren can focus their efforts on serving the students, involve all members of the pesantren in continuous improvement, and ensure that every process runs efficiently and effectively. Core TQM concepts, such as organizational member participation, fact-based decision-making, and continuous improvement, are explained in the context of their implementation in pesantren. Practical steps for applying TQM in pesantren are also presented, including initial assessment, quality goal setting, training and development, and continuous evaluation. It is hoped that by adopting the TQM approach, pesantren can improve service quality, strengthen relationships with stakeholders, and ensure the long-term sustainability of the institution.